James Dodson Barbee and David Rankin Barbee papers - Barbee, James Dodson, 1832-1904.; Barbee, David Rankin, 1874-1958.; Bledsoe, Albert Taylor, 1809-1877.; Plitt, George
Correspondence, diaries, manuscripts of sermons, notes, notebooks, account books, printed matter, photographs, and other papers relating chiefly to the Methodist Publishing House, Nashville, Tenn., and to claims of the Methodist Episcopal Church, South, growing out of Civil War property confiscations. Subjects include the All Souls Memorial Episcopal Church, Washington, D.C.; Cleveland Park Memorial Library, Washington, D.C.; Jefferson Davis; and slavery. Correspondents include John Whitfield Cunningham, Virginius Dabney, Collins Denny, Waddy T. Duncan, William Wallace Duncan, E.E. Hoss, John Christian Keener, James Craik Morris, Elbert C. Reeves, and members of the Barbee family.
The Historical File includes the papers of George Plitt consisting chiefly of correspondence of or concerning James Buchanan and the papers of Albert Taylor Bledsoe.
Microfilm edition of George Plitt papers available
Microfilm reproduced from originals in private hands.
Private
Microfilm edition of Albert Taylor Bledsoe papers available
Microfilm of originals in the University of Virginia (Charlottesville).
Virginia: University of Virginia, Charlottesville.
Keywords: Buchanan, James, -- 1791-1868 -- Correspondence; Cunningham, John Whitfield, -- 1805-1874 -- Correspondence; Dabney, Virginius, -- 1835-1894 -- Correspondence; Davis, Jefferson, -- 1808-1889.; Denny, Collins, -- 1854-1943 -- Correspondence; Duncan, Waddy T. -- 1867- -- Correspondence; Duncan, William Wallace -- Correspondence; Hoss, E. E. -- 1849-1919 -- Correspondence; Keener, John Christian, -- 1819-1906 -- Correspondence; Morris, James Craik, -- 1870-1944 -- Correspondence; Reeves, Elbert C., -- 1841-1929 -- Correspondence; Barbee family -- Correspondence; All Souls Memorial Episcopal Church (Washington, D.C.); Cleveland Park Memorial Library; Methodist Episcopal Church, South; Methodist Publishing House; Methodist Church -- Tennessee; African Americans; Publishers and publishing -- Tennessee -- Nashville; Religious literature; Slavery -- United States; United States -- History -- Civil War, 1861-1865 -- Claims; United States -- History -- Civil War, 1861-1865 -- Religious aspects; Editors; Historians